Ontology-based IT pedagogical knowledge framework - Chin, Kum; Chang, Elizabeth; Atkinson, Douglas; Parker, K. (Informing Science Institute, 2007)
Prospective students often have trouble differentiating between many computer-related programs of study such as computer science (CS), information systems (IS), information engineering (IE), software engineering (SE), information technology (IT), electronic commerce (EC), computer engineering (CE), etc. To compound the problem many institutions offer programs with similar names but with different content, or programs with different names but with similar content. The extensive overlap in course content in many computing-focused disciplines has even created confusion among academics. This paper first reviews relevant literature on the topic and then presents a high-level view of an Information Technology (IT) Pedagogical Knowledge framework from an ontological point of view.